2019
DOI: 10.1021/acs.jchemed.9b00292
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Feedstocks, Processes, and Products in the Teaching Laboratory: A Framework for Students To Use Metrics to Design Greener Chemistry Experiments

Abstract: Exciting developments in the field of Green Chemistry spur the continuous innovation of experiments in the teaching laboratory. Beyond learning practical techniques, students can critically assess experiments using relevant metrics to propose further improvements and identify the most important interconnected impacts of these alternative products and processes. Herein we review popular laboratory experiments through the simple framework of feedstocks, processes, and products, offering data-driven methods for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 160 publications
(331 reference statements)
0
17
0
Order By: Relevance
“…Here, we can include these components in our determination of an intensive efficiency metric similar to yield for a reaction. To do this, we can employ many different green chemistry metrics, , though process mass efficiency (PME), the ratio of the mass of the product ( x ) to the total mass of the inputs ( u ), is appropriate for the first-semester undergraduate chemistry classroom (eqs and ) …”
Section: Expanding the Reaction System: From Yield To Process Mass Ef...mentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we can include these components in our determination of an intensive efficiency metric similar to yield for a reaction. To do this, we can employ many different green chemistry metrics, , though process mass efficiency (PME), the ratio of the mass of the product ( x ) to the total mass of the inputs ( u ), is appropriate for the first-semester undergraduate chemistry classroom (eqs and ) …”
Section: Expanding the Reaction System: From Yield To Process Mass Ef...mentioning
confidence: 99%
“…They serve to quantitatively assess the 12 principles of green chemistry which focus on distinctive areas including the safety and sustainability of reagents and products and help us evaluate different chemical transformations. By using metrics found in green chemistry research and related fields addressing sustainability, chemists and educators have the tools to better design and assess the chemicals they create and the systems they encounter. Found in both lecture and laboratory, in majors classes, and in special topics courses, , green chemistry principles may also be used in general chemistry to explore foundational chemistry concepts such as amounts, concentration, and energy . Examining these measures and metrics through the lens of extensive and intensive properties, , it is possible to identify relevant metrics early on in the chemistry curriculum and use sustainability metrics as tools to connect concepts throughout the course, to other courses, and real-world examples. , …”
Section: Introductionmentioning
confidence: 99%
“…For students with an undergraduate chemistry background, the 12 Principles of Green Chemistry (Figure ) serve as an excellent framework to teach topics of green chemistry and chemical safety. For public outreach or younger K–12 audiences, Colby faculty and students rely on a simpler three-part framework: feedstocks, processes, and products . For feedstocks, students are asked where our raw materials come from: renewable or depleting sources?…”
Section: Green Chemistry Safety and Student Chaptersmentioning
confidence: 99%
“…For public outreach or younger K−12 audiences, Colby faculty and students rely on a simpler threepart framework: feedstocks, processes, and products. 44 For feedstocks, students are asked where our raw materials come from: renewable or depleting sources? For processes, students are asked how much energy is being used?…”
Section: Colby Collegementioning
confidence: 99%
“…Previous review articles have reported on various aspects of the use of green chemistry in education, e.g., laboratory work in tertiary education [12,27,[52][53][54][55][56][57][58][59], often only in a specific field of chemistry [52,56,57], and the integration of selected green chemistry principles into laboratory work in tertiary education [53,56,57]. The present paper aims to review experimental work from green chemistry perspectives more holistically by involving all fields of chemistry, all educational levels, and 12 Principles of Green Chemistry in a 25-year long period.…”
Section: Introductionmentioning
confidence: 99%